2014
DOI: 10.1021/bm500521j
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Chemosensitizing Activity of Amphiphilic Poly(glycerol)–Poly(alkylene oxide) Block Copolymers

Abstract: All polymeric chemosensitizers proposed thus far have a linear poly(ethylene glycol) (PEG) hydrophilic block. To testify whether precisely this chemical structure and architecture of the hydrophilic block is a prerequisite for chemosensitization, we tested a series of novel block copolymers containing a hyperbranched polyglycerol segment as a hydrophilic block (PPO-NG copolymers) on multi-drug-resistant (MDR) tumor cells in culture. PPO-NG copolymers inhibited MDR of three cell lines, indicating that the linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
1
30
1
1
Order By: Relevance
“…Similar effects have been observed for polyethoxylated surfactants containing hydrocarbon radicals . Recently, it has been shown that block copolymers of poly(propylene oxide) (PPO) and hyperbranched polyglycerol and those of PDMS and poly(ethylene oxide) (PEO) are also able to suppress MDR tumor cells. Systematic studies performed by Kabanov and coworkers revealed that the potency of Pluronics in inhibiting MDR cells strongly depends on their structure.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Similar effects have been observed for polyethoxylated surfactants containing hydrocarbon radicals . Recently, it has been shown that block copolymers of poly(propylene oxide) (PPO) and hyperbranched polyglycerol and those of PDMS and poly(ethylene oxide) (PEO) are also able to suppress MDR tumor cells. Systematic studies performed by Kabanov and coworkers revealed that the potency of Pluronics in inhibiting MDR cells strongly depends on their structure.…”
Section: Introductionsupporting
confidence: 62%
“…3 H‐labeled copolymers were incubated with MDR human breast adenocarcinoma MCF‐7/ADR cells. This cell line was chosen because it has been routinely used in our group for the analysis of cytotoxicity and chemosensitizing properties of the copolymers studied in this report …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphiphilic copolymers can self‐assemble in aqueous solution to form micelles with hydrophobic segments as the inner core and hydrophilic segments as the outer shell . The hydrophobic core can act as a storage for encapsulating water‐insoluble drugs, which can reduce toxic side effects of entrapped drugs to healthy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Linear–dendritic copolymers show some different features when compared to linear block copolymers with the same molecular weight including lower hydrodynamic volumes, high circulation times in the bloodstream, a large number of functional groups on their surfaces and interior voids for the attachment and encapsulation of active moieties, high loading capacities and different in vivo and in vitro cytotoxicity due to their rigid structures . Due to their unique properties, different types of linear–dendritic copolymers have been synthesized for special applications including catalysis, drug carrying and membrane preparation . Recently, the design and synthesis of linear–dendritic copolymers with aliphatic polyether backbone like poly(ethylene glycol) (PEG) have attracted great attention.…”
Section: Introductionmentioning
confidence: 99%